MODERN ASPECT OF OBESITY PREVENTION - Schepin, S.; Artemiev, M.; Antonets, O. (Rehabilitation and Recreation, 2022)
Obesity is a common chronic disease with serious medical consequences. The treatment of obesity is a complex and underdeveloped problem, the solution of which not only improves the quality of patients` lives and increases life expectancy, but also significantly reduces morbidity and mortality complications. The purpose of the study is to demonstrate possible options for improving the prevention and care of patients with obesity and overweight. To achieve the goals set, the following tasks have been solved: analysis of the incidence of obesity and overweight among Ukrainian adult population and factors contributing to their development; the existing treatment systems of patients with obesity and overweight have been analyzed. It has been established that the main goals of the obesity treatment, along with weight loss, are to prevent or alleviate concomitant diseases the development, primarily the cardiovascular system, and improve the patient's quality of life. A number of diet therapy methods in the presence of this disease have been proposed. Conclusions: 1. In Ukraine, there is a need to improve the provision of rehabilitation care to patients with obesity and overweight due to its high prevalence among various social groups and risk factors for obesity. 2. The low efficiency of health care institutions providing medical and preventive care to patients with obesity and overweight is associated with insufficient knowledge of the pathological and physiological aspects of the disease developing by medical personnel, non-compliance with WHO recommendations for obesity treatment, and lack of motivation. 3. The needs for treatment and preventive care of patients with obesity do not correspond to the structure and quantity underlying the development of effective organizational and functional models for rehabilitation care organization improving for patients.